Substance use and risky sexual behaviours among sexually experienced Ghanaian youth - Doku, David (BioMed Central, 2012)
BACKGROUND: The association between risky sexual behaviours and substance uses among Ghanaian youth were investigated. METHODS: An in-school cross-sectional representative survey was conducted among 12-18-year- old youth in Ghana in 2008 (N = 1195, response rate =90%). Logistic regression analyses were employed to investigate the association between substance use (tobacco use, drunkenness, marijuana use and other drug uses) and risky sexual behaviours (sexual debut, condom use and number of sexual partners). RESULTS: Of all youth, 25% (28% boys and 23% girls) were sexually experienced. The mean age for first sexual intercourse was 14.8 years (14.4 years for boys and 15.1 years for girls). Among the sexually experienced, 31% had multiple sexual partners. Older age (OR = 3.4, 95% CI = 1.7-3.4) and rural residency (OR = 1.5, 95% CI = 1.1-2.1) were independently associated with sexual debut while only older age (OR = 2.4, 95% CI = 1.7-3.4) was associated with condom use. Additionally, smoking (OR = 3.7, 95% CI = 2.0-6.8), tawa use (OR = 2.4, 95% CI = 1.3-4.7), tobacco use (OR = 2.8, 95% CI = 1.7-4.7) drunkenness (OR = 1.7, 95% CI = 1.1-2.8) and marijuana use (OR = 3.3, 95% CI = 1.6-7.0) were independently associated with sexual debut. Furthermore, all substance uses studied were associated with having one or multiple sexual partners. CONCLUSION: Substance use seems to be a gateway for risky sexual behaviours among Ghanaian youth. Public health interventions should take into account the likelihood of substance use among sexually experienced youth.